Serum Visinin-Like Protein 1 Is a Better Biomarker Than Neuron-Specific Enolase for Seizure-Induced Neuronal Injury: A Prospective and Observational Study - Tan, Zheren; Jiang, Jianlin; Tian, Fafa; Peng, Jinxin; Yang, Zhiquan; Li, Shuyu; Long, Xiaoyan (Frontiers in Neurology, 2020)
Introduction: Visinin-like protein 1 (VILIP-1) is an established biomarker of neuronal injury. The levels of serum VILIP-1, neuron-specific enolase (NSE) and caveolin-1 (CAV-1) were measured to investigate potential of VILIP-1 as a biomarker for seizure-induced neuronal injury, and the correlation of VILIP-1 with severity of epilepsy and blood-brain barrier dysfunction were investigated. Materials and Methods: Patient with epilepsy from 14 to 70 years of age and age-, sex-matched healthy subjects were involved in this study. All blood sample of patients were collected within 3-72 h after the seizure. The severity of epilepsy and levels of serum VILIP-1, NSE and CAV-1 were measured. Accuracy of VILIP-1 and NSE was obtained from receiver operating curve analyses. Associations between VILIP-1 and severity of epilepsy, VILIP-1 and CAV-1 were investigated. Results: A total of 58 patients and 29 healthy control subjects were included in our study. The levels of serum VILIP-1, NSE and CAV-1 in the patient group were significantly higher than those in the control group. VILIP-1 has higher and significant accuracy for assessing seizure-induced neuronal injury compared with NSE. VILIP-1 levels were positively associated with severity of epilepsy and CAV-1 in patients with epilepsy. Conclusions: VILIP-1 may be a better serum biomarker than NSE for assessing seizure-induced neuronal injury and even brain injury caused by various pathological condition. Further studies are required to explore the clinical contribution of VILIP-1 in diagnosis, treatment strategies and outcome assessments of epilepsy.